Cervical Cancer and Cervical Cancer Screening in Women with HIV in Guangxi, China: A Model Simulation Study - Ran Zhao; Shalini Kulasingam (MDM Policy & Practice)
Background. Cervical cancer screening can effectively reduce the disease burden. In China, the current cervical cancer screening guidelines do not provide separate screening recommendations for women living with HIV (WLWH) to account for their increased risk. Methods. We developed a comprehensive individual-based simulation model to provide evidence to support tailored cervical cancer screening programs for WLWH in Guangxi, a region with a high prevalence of HIV in China. Compared with the current screening coverage (i.e., the status quo), we evaluated the benefits and the harms associated with 9 cytology-based cervical cancer screenings tailored to WLWH in Guangxi. The 9 strategies vary in terms of screening interval (every 1, 3, or 5 y) and the age to exit screening (at age 65 y, 85 y, or no exit). Results. All screening strategies evaluated were effective in reducing cervical cancers and cancer deaths among WLWH. Compared with the status quo, the percentage reduction in total cancers ranged from 18% to 60%, and the percentage reduction in cancer deaths ranged from 20% to 62%. Strategies with a 3- or 5-y screening interval had lower numbers of colposcopies per cancer and cancer deaths prevented. Conclusion. Implementing cytology-based cervical cancer screening among WLWH in Guangxi, China, can effectively prevent cervical cancer cases and cancer deaths. Our results suggest that adopting an older end age and a shorter screening interval might be more effective in preventing cancer cases and deaths but may also be associated with more screenings and potential harms and costs, while adopting a 3- or 5-y screening interval may provide a more reasonable balance of benefits and harms to prevent future cancer cases and deaths among WLWH in Guangxi, China. Highlights Our comprehensive model can be used to evaluate various health interventions that aim to reduce the disease burden caused by HPV and cervical cancer. Cytology-based cervical cancer screening tailored to WLWH in Guangxi, China can effectively prevent cervical cancer cases and cancer deaths. Adopting a 3- or 5-y screening interval may provide a more reasonable balance of benefits and harms to prevent future cancer cases and deaths.